THE DEVELOPMENT OF CITIZEN PROJECT LEARNING MODEL FOR EDUCATION CHARACTER IN HIGHER EDUCATION - Anita Trisiana, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This research aims at analyzing the strategy development the Citizen Project learning model for education character in Higher Education. Methods used in this research and development which is combined with data triangulation analysis, conducted at Universitas SlametRiyadi Surakarta, involving faculty and students who participate in Citizenship Education courses. It was a research method used to produce a particular product and test the effectiveness validity of the product. The funding shows that the development of the Citizen Project model in higher education produced the effective reinforcement and intellectual attitudes based on the civic education competence that is civic knowledge, civic skills, and civic disposition. The improvement and development of life skills which is realized through the achievement of students’ competence, to survive, adapt and succeed in life. Instructional Materials based on character values believed by the nation of Indonesia contributed to the development of the government model policy in implementing character education in universities. The improvement is to provide the basic knowledge, skills, learning experiences that build social integrity and realize the character national. In accordance with the quality improvement realization and education relevance which should be done thoroughly, the improvement covers the development of Indonesia fully human dimension, namely moral aspects, attitude, manners, knowledge, skills, and culture. Development of those aspects leads to life skills improvement and development which is realized through the student competence achievement, to survive and adapt and succeed in life.